Spanish registry of cardiac resynchronization therapy in adults with congenital heart disease (RETRACCA): clinical outcomes at one year follow-up. (19th May 2022) - Peinado, R; Cano, O; Rivas-Gandara, N; Alvarez-Ortega, C; Garcia-Orta, R; Diaz-Infante, E; Segura-De La Cal, T; Lopez-Ledesma, B; Cantalapiedra-Romero, J; Macias, R; Rueda, J; Dos-Subira, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Spanish Society of Cardiology Background: There are limited data about the impact of cardiac resynchronization therapy (CRT) in adults with congenital heart disease (CHD) with conflicting results in patients (P) with systemic right ventricle (SRV). Objectives: We analyzed the one-year outcomes of adults with CHD implanted with CRT and the impact of CRT in P with SRV as compared with systemic left ventricle (SLV). Methods: Data were analyzed from the Spanish Registry of CRT in adults with CHD (RETRACCA). This is an observational, ambispective (66 % retrospective), multicenter Registry, including 74 adults with CHD implanted with a CRT device from 6 Spanish centers from 2007 to 2021. Ventricular function was assessed by echocardiography and graded on a four-point ordinal scale. Response to CRT was defined as an improvement in NYHA functional class and/or systemic ventricular ejection fraction by at least one category. In addition to changes in functional class and ventricular function, other outcomes analyzed included mortality, heart transplantation and CRT-related complications. Results: 68 P completed one year of follow-up. Table 1 shows the baseline characteristics of the P prior to CRT. The two main indications for CRT were depressed systolic function of the systemic ventricle with more than 40 % ventricular pacing (69 %) and severely depressed systolic function of systemic ventricle, NYHA FC II-IV and QRS > 150 (18 %). Sixty percent of P received a CRT-ICD, whereas 40 % received a CRT-pacemaker. The approach for CRT system implantation was transvenous in 70 % of the patients, mixed in 21 % and fully epicardial in 9 %. Overall, 43 out of 68 patients (75 %) responded to CRT either by improvement of NYHA FC (56 %) and/or systemic ventricular function (41 %). Compared with baseline, CRT was associated with significant improvement in NYHA FC (p<0.001; figure 1), QRS duration (169±31 vs 150±29; p=0.005), and systemic ventricle systolic function (severe or moderate 80 % vs 58 %; p=0.04). Percentage of responders was similar among patients with a SLV (73 %) and with SRV (81 %; p=0.51). Only pre-implant NYHA FC III-IV was predictive of a positive response in the univariate analysis (OR 3.82; 95 % CI 1.03-14.18). Seven complications occurred at implant (10 %). During the follow-up, there were 8 complications in 7 P: 2 P had heart transplantation, 3 P required hospital admission for decompensation of heart failure, 2 P presented pocket infections and 1 lead malfunction. No differences in complication rates were observed between the systemic LV and systemic RV subgroups. Conclusions: In this series, at one-year follow-up, CRT resulted in improvement in functional class and/or systemic ventricular function in 75 % of P with adult CHD. The percentages of responders and complications were similar among patients with SLV or SRV.